A case report of lameness in two dairy goat herds; a suspected combination of nutritional factors concurrent with treponeme infection. (December 2015) - Groenevelt, Margit; Anzuino, Katharine; Smith, Sue; Lee, Michael; Grogono-Thomas, Rosemary
Abstract Background Two dairy goat farms with high level of lameness in lactating animals were presented for further investigation. Farm 1 and Farm 2 presented with 37 and 67 % morbidity, respectively. Both farms had an all year round indoor system, feeding ad libitum concentrate with forage available at all times. Case presentation The lameness was found to be based in the foot. Previous treatments consisting of biweekly footbathing with zinc sulphate, spraying lesions with oxytetracycline spray and packing lesions with copper crystals on a single occasion and single injections with long acting oxytetracycline had not been successful. Mild cases had signs of haemorrhaging in the white line or on the sole of the foot. Moderate cases showed under running of the wall horn or small areas of exposed sole corium. Severe cases would consist of horn or wall separation with the corium exposed and infected. In extreme cases only the wall horn of the claw remained, with a large area of necrotic tissue in the centre and no healthy corium visible. Only one animal was seen to have interdigital lesions. Polymerase chain reaction (PCR) and culture of swabs taken from exposed corium and the interdigital space were negative forDichelobacter nodosus but PCR for treponemes were positive in both the adults and the youngstock tested. Due to the high level of concentrate in the diet of these goats, nutrition was thought to contribute to the problem. Transcutaneous rumen fluid samples were taken and pH was measured on both farms, with 35 % of the samples below pH value 5.5. Conclusion No definite diagnosis could be made. However, the results suggest both treponemes and nutrition play a role in the aetiology of the lameness. The initial sole or wall horn lesions were thought to be secondarily infected by treponemes. Further investigation is needed to definitively diagnose the cause and contributing factors for this lameness.